Perhitungan Poros Roda Depan Motor Supra X 100CC - Nur Hady Iskandar Lakxena; Deri Teguh Santoso; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
In a machine there is a number of components in it there are many. All these components work together to produce a movement. A malfunction in one of the components will result in a machine not working normally which causes an accident. The shaft is a solid cylindrical engine element that serves as a seat for other elements such as pulleys, sprockets, gears, clutches and also acts as an element of transmitting power and rotation of the driving engine. Almost all machines that contain moving or rotating mechanisms have shafts, from small to large shafts. Many things must be considered in designing a component of a machine. Therefore, in this study, the design of the Supra X 100 CC Front Wheel Axle was carried out. The method used is direct observation of objects, Literature Studies, Internet Information by searching from several journals or other supporting media. The material used is S40C carbon steel construction with a tensile strength of 55 kg/mm2, the comparison value of (τa x Sf2)/β is 4.27 kg/mm2 and the comparison value of * Cb * Kt is 4.57 kg/mm2 . The shaft diameter is obtained 14 mm then the shaft material is S40C by normalizing heat treatment, with a fillet radius of 1 mm and the size and keyway of 5 * 5 * 5 * 0.25. The external load of the motor from the calculation is W1 = 950 N and W2 = 1000 N and Fay = 711.95 N and Fby = 1238.05 N. The results of the loading on the shaft are F1 = F2 = 355.975 N and and Fay = 711.95 N